Kronologi Bahasa Arab Semitik Perspektif Historis - Rofik, Eka Nur (Institut Agama Islam Riyadlatul Mujahidin (IAIRM) Ngabar Ponorogo, Indonesia, 2021)
Arabic comes from the Semitic language family. it has a higher position than other Semitic languages ​​because it is not extinct even though it is thousands of years old. Arabic is one of the most widely spoken languages ​​today. Users are not only Muslims but also non-Muslims. Semitic is a language family associated with one of the sons of the Prophet Noah a.s. namely Sam son of Noah. In the narration, it is stated that Noah had three children, namely Sam (Semitic), Yafit (Aramiyah), and Ham (Hamiyah). Languages ​​belonging to the Semitic language family experience slow development. Some languages, such as Akkadian, have even become extinct. and other languages, although not extinct but the speakers are no longer a big nation. This language is only spoken by a small number of people, like Aramaic. Only Arabic, the only Semitic language, has survived thousands of years. Arabic users continue to grow even today. The final conclusion of this paper is that Arabic represents other Semitic languages, both in terms of their origin and in terms of their privilege.